Effect of metal chloride pre-cursor on the structure of Yb-Doped Ba(Ce, Zr)O3 ceramics electrolyte: a comparative study with different metal salts - Osman, N.; Yaakob, M.H.; Talib, I.A. (Universiti Kebangsaan Malaysia, 2014)
This paper discusses the effect of a metal chloride pre-cursor on the phase formation of Yb-doped Ba(Ce, Zr)O3 solid electrolyte derived from a sol-gel method via acetate and chloride salts. The use of metal chloride as a pre-cursor showed the increased in thermal decomposition temperature (Ttd≈1360oC) compared to the metal nitrate pre-cursor (Ttd≈1280oC) and (b) leading to the formation of impurity phases. At calcination temperature of 1500oC, the sample prepared from metal chloride did not form a single-phase of Ba(Ce, Zr)O3. Impurity phases of BaCl2, BaCO3 and (Ce, Zr)O2 were detected in the sample as proven by XRD result. A high purity compound at relatively lower temperature (T=1400oC) was only obtained for the sample that prepared from metal nitrate compared to acetate and chloride (T>1500oC) and carbonate and oxide (T=1500oC) pre-cursors.